Adolescent and young adult childhood cancer survivors' preferences for screening and education of sexual function. Issue 12 (10th July 2021) - Sopfe, Jenna; Marsh, Rebekah; Frederick, Natasha N.; Klosky, James L.; Chow, Eric J.; Dorsey Holliman, Brooke; Peterson, Pamela N.
Abstract: Background: Sexual dysfunction (SD) is a common yet underrecognized concern among childhood cancer survivors (CCS). CCS who are now adolescent and young adult (AYA‐CCS) identify SD as an unmet need. This study sought to explore AYA‐CCS preferences on how, when, where, and by whom SD‐focused communication should occur. Procedure: This qualitative study utilized semi‐structured interviews to explore AYA‐CCS (now aged 15–24 years) experiences with, and preferences for, SD conversations. Thematic analysis methodology guided interpretation; themes were clustered into categories of who, how, when, and where SD conversations should occur. Results: AYA‐CCS highlighted the importance of patient–provider rapport to facilitate SD conversations, but did not have consistent preferences regarding provider type or specialty. Providers should reduce discomfort by normalizing ongoing, personalized conversations. Some AYA‐CCS mentioned that notification that such a conversation is going to occur would be appreciated, and most were in favor of a screening tool to facilitate conversations. Preferences for when and where SD conversations should occur were centered on maximizing privacy. Conclusions: SD is an inadequately addressed concern in AYA‐CCS, and providers must familiarize themselves with AYA‐CCS preferences for discussing SD to reduce communication barriers and address this unmet need. In addition to corroborating prior studies' findings such as normalizing ongoing SD conversations, this study demonstrated novel ideas for reducing barriers, including use of a notification to prepare them prior to SD conversations, favoring the use of a screening tool, and the importance of establishing rapport prior to the SD conversations.